SOCIAL LIVING STANDARD AND PROBLEMS OF THE RURAL AND URBAN POPULATION OF KHOREZM (1925-1941) (TAMADDUN NURI JURNALI, 2025)
This article analyzes social processes in the villages and cities of the Uzbek SSR in 1925-1941, in particular, the implementation of measures to eliminate illiteracy, women's liberation, and the state of medicine using the example of Khorezm.